Features of physiological processes in migrants and indigenous population of Ugra (Russia) - KUCHIN, R.V.; STOGOV, M.V. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Amid the climatic and geographic conditions of the Northern territories, the human body, especially from migrants, is influenced by unusual, excessive and harsh environmental factors that are irrelevant to its nature. The current situation shows that the social and economic losses that entail conditions associated with a decrease in the population adaptability, especially non-indigenous, leads to the need not only to study the mechanisms of physiological changes in the residents of the Northern regions, but also to find ways to prevent diseases in the descendants of migrants living in the North of the Russian Federation. RESUMEN En medio de las condiciones climáticas y geográficas de los territorios del norte, el cuerpo humano, especialmente el de los migrantes, está influenciado por factores ambientales inusuales, excesivos y severos que son irrelevantes para su naturaleza. La situación actual muestra que las pérdidas sociales y económicas que conllevan condiciones asociadas con una disminución de la adaptabilidad de la población, especialmente los no indígenas, lleva a la necesidad no solo de estudiar los mecanismos de cambios fisiológicos en los residentes de las regiones del norte, sino también encontrar formas de prevenir enfermedades de los descendientes inmigrantes que viven en el norte de la Federación de Rusia.